Hodgkin Lymphoma Presenting With Spinal Cord Compression: Challenges for Diagnosis and Initial Management. (March 2022) - Bloxham, Nicola; Cross, Justin; Garnett, Matthew; Bewick, Jessica; Armon, Kate; Hook, C Elizabeth; Murray, Matthew J
Hodgkin lymphoma (HL) can present with extra-nodal disease, but spinal cord compression is exceptionally rare. We describe a 15-year-old presenting with hip/back pain with normal initial examination. Persistent pain and raised inflammatory markers prompted further investigation with MRI, which revealed an epidural mass causing spinal cord compression. On examination, there was no palpable lymphadenopathy or cauda equina syndrome, but absent lower limb reflexes were noted. Following multidisciplinary discussion, it was determined that cauda equina syndrome was imminent and therefore surgical debulking was undertaken, both to prevent this complication and establish a diagnosis. At surgery, the tumor was highly vascular. Frozen section confirmed lesional material. Following surgery, and given the frozen section findings, a short course of steroids was commenced to reduce any peri-surgical edema. Unfortunately, histopathology was ultimately non-diagnostic, due to failure of immunohistochemistry on technically challenging material. Consequently, ultrasound-guided excision biopsy of a (non-palpable) cervical lymph node was performed five days later; histopathology showed typical effacement of the normal architecture and a conspicuous population of CD15/CD30-positive larger pale cells present, confirming nodular sclerosis classic HL, despite recent steroids. We review the available literature for HL presenting with spinal cord compression and describe the challenges for diagnosis and initial management in such cases.